Career Choices for Education Students After Completing Studies - Guslianto, Guslianto; Batubara, Aisyah Nur; Hasnah, Hasnah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
This research aims to analyze education students' career choices after completing their studies. This research uses quantitative methods with a correlation research type. This research was conducted by distributing questionnaires to one hundred respondents. Data were analyzed by Miles and Huberman. The research results found that 35% became teachers, 30% became lecturers, 9% became entrepreneurs, 7% became tailors, 4% became employees, 4% became marketing, 3% became designers, 5% became architects, and 3% others. The results of this research can be used as initial data for future researchers in studying this problem in the context of different issues.